Development strategy and lessons learned for a 10-valent pneumococcal conjugate vaccine (PNEUMOSIL®). Issue 8 (3rd August 2021) - Alderson, Mark R.; Sethna, Vistasp; Newhouse, Lauren C.; Lamola, Steve; Dhere, Rajeev
ABSTRACT: Pneumococcal conjugate vaccines (PCVs) have proven to be the best way to prevent severe childhood pneumococcal disease but until recently have been difficult for many countries to afford sustainably. In 2008, the Serum Institute of India, Pvt. Ltd. and PATH entered into a collaboration, funded in part by the Bill & Melinda Gates Foundation, to respond to this problem by developing a PCV designed to be affordable, accessible, and protective against the pneumococcal serotypes causing the most morbidity and mortality in low- and middle-income countries. The resulting 10-valent PCV ( PNEUMOSIL® ) received World Health Organization prequalification in December 2019 – making it just the third PCV to be certified as an option for Gavi, the Vaccine Alliance-eligible countries – and is being made available at a Gavi price of US2/dose. The task of developing a state-of-the-art, yet lower-priced, PCV required public-private collaboration across geographies and yielded a variety of successes and learnings useful to the vaccine development field. Key among the learnings were factors related to manufacturing strategy and optimization, serotype selection, flexibility, early risk detection and mitigation, partner trust and continuity across similar-class products, complementary business philosophies, and early clarity of purpose.